Quantifying Extremely Rapid Flux Enhancements of Radiation Belt Relativistic Electrons Associated With Radial Diffusion - Si Liu; Qi Yan; Chang Yang; Qinghua Zhou; Zhaoguo He; Yihua He; Zhonglei Gao; Fuliang Xiao (Geophysical Research Letters)
Abstract Previous studies have revealed a typical picture that seed electrons are transported inward under the drive of radial diffusion and then accelerated via chorus to relativistic energies. Here we show a potentially different process during the 2–3 October 2013 storm when Van Allen Probes observed extremely rapid (by about 50 times in 2 h) flux enhancements of relativistic (1.8–3.4 MeV) electrons but without distinct chorus at lower L‐shells. Meanwhile, Time History of Events and Macroscale Interactions during Substorms satellites simultaneously measured enhanced chorus and fluxes of energetic (∼100–300 keV) seed electrons at higher L‐shells. Numerical calculations show that chorus can efficiently accelerate seed electrons at L ∼ 8.3. Then radial diffusion further increased the phase space density of relativistic electrons throughout the outer radiation belts, with a remarkable agreement with the observation in magnitude and timescale. The current results provide a different physical scenario on the interplay between radial diffusion and local acceleration in outer radiation belt.